2014
DOI: 10.1111/ajd.12157
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the lipase‐H gene causing autosomal recessive hypotrichosis and woolly hair

Abstract: Hypotrichosis is characterised by sparse scalp hair, sparse to absent eyebrows and eyelashes, or absence of hair from other parts of the body. In few cases, the condition is associated with tightly curled woolly scalp hair. The present study searched for disease-causing sequence variants in the genes in four Pakistani lineal consanguineous families exhibiting features of hypotrichosis or woolly hair. A haplotype analysis established links in all four families to the LIPH gene located on chromosome 3q27.2. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The LIPH variant (p.Gln230*) and the LPAR6 variants (p.Phe24Hisfs*29 and p.Asp63Val) perfectly segregating with the disease phenotype in the families of the present report. Prior to the present study, Mehmood et al (2015Mehmood et al ( , 2016 and Khan et al (2011) from our group reported variants in the LIPH and LPAR6 genes in consanguineous families of Pakistani origin, displaying the features similar to those observed in the present families. Lipase H is a member of triglyceride lipase gene family was cloned and characterized by Sonoda et al (2002), and composed of 10 exons in an approximately 45-kb region encodes a protein of 451 amino acids with a predicted molecular mass of 50,859 Da.…”
Section: Discussionsupporting
confidence: 84%
“…The LIPH variant (p.Gln230*) and the LPAR6 variants (p.Phe24Hisfs*29 and p.Asp63Val) perfectly segregating with the disease phenotype in the families of the present report. Prior to the present study, Mehmood et al (2015Mehmood et al ( , 2016 and Khan et al (2011) from our group reported variants in the LIPH and LPAR6 genes in consanguineous families of Pakistani origin, displaying the features similar to those observed in the present families. Lipase H is a member of triglyceride lipase gene family was cloned and characterized by Sonoda et al (2002), and composed of 10 exons in an approximately 45-kb region encodes a protein of 451 amino acids with a predicted molecular mass of 50,859 Da.…”
Section: Discussionsupporting
confidence: 84%
“…The LIPH gene encodes a 55‐kD protein comprising a lipase domain (signal peptide), lid region (7–12 amino acids), B9 loop, hinge region, and plate domain . The hinge region is involved in making a link between the N and C terminals of the LIPH protein.…”
Section: Discussionmentioning
confidence: 99%
“…5 In family c, microsatellite markers-based genotyping and dideoxy chain termination sequencing were performed as described by Mehmood et al . 6 Analysis of SNPs genotyping in two families (a and b) and microsatellite markers generated haplotype in family c established a linkage on chromosome 6p22.3-p21.2. Exome and Sanger dideoxy chain termination sequencing revealed a novel transversion variant c.102C>A (p.Asp34Glu) in the PNPLA1 gene located on chromosome 6p21.31 that co-segregated with ARCI in the families.…”
Section: Editormentioning
confidence: 99%